Translating English Euphemisms into Arabic: Challenges and Strategies - Abdalla, Manar Abdelhafeeth (2009)
A Master of Arts Thesis in Translation and Interpreting (English / Arabic / English) by Manar Abdelhafeeth Abdalla Entitled, "Translating English Euphemisms into Arabic: Challenges and Strategies," May 2009. Available are both Hard and Soft Copies of the Thesis.